Business continuity for times of vulnerability : empirical evidence - Sánchez, Marisa Analía (John Wiley & Sons, 2023)
Organizations operate in environments of vulnerability. While there are methodologies that guide business continuity management, it is evident that organizations remain vulnerable to disruptions emerging in times of transformation and systemic change. This work aims to compile and analyze the disruptions and related risk management strategies or activities described in the literature, and explore which disruptions are creating concern in companies and how they approach them. The methodology is based on a review of the literature and from the review we define a questionnaire to guide semi‐structured interviews to managers from companies all located in a highly volatile macroeconomic context. The literature describes disruptions related with governance, cyberattacks, technology, supply chain, internal processes, and shock events and both precrises and postcrises strategies. The empirical analysis using data from companies reveals that (a) the most stressful disruptions are the currency devaluation, the high inflation rate, and government interventions and (b) managers rely on collaborative work, effective communication between stakeholders, supportive leadership, and constant adaptation to the new environment. Future research is required on techniques supporting adaptation to ‘new normalcy’.